2020
DOI: 10.1038/s41598-020-62602-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of cellular events related to mitochondrial burnout leading to cell death in Fuchs endothelial corneal dystrophy

Abstract: fuchs endothelial corneal dystrophy (fecD) is a degenerative eye disease characterized by corneal endothelial cell (CEC) death and the formation of guttae, an abnormal thickening of CEC's basement membrane. At the tissue level, an oxidative stress causing mitochondrial damage and CEC death have been described to explain FECD pathogenesis. At the cellular level, our group has previously observed significant variability in the mitochondrial mass of FECD CECs. This led us to hypothesize that mitochondrial mass va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Mitochondrial dynamics consists of a coordinated cycle of mitochondrial fusion and fission to maintain its shape and size. Abnormal mitochondrial dynamics in FECD comprises aberrant mitochondrial fusion including decline in mitofusin 2, loss of mitochondrial mass [15,16], and fission including increased mitochondrial fission proteins indicative of fragmentation [18], and activation of mitochondrial-mediated intrinsic apoptosis pathway [11].…”
Section: Mitochondrial Dysfunction In Fecdmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dynamics consists of a coordinated cycle of mitochondrial fusion and fission to maintain its shape and size. Abnormal mitochondrial dynamics in FECD comprises aberrant mitochondrial fusion including decline in mitofusin 2, loss of mitochondrial mass [15,16], and fission including increased mitochondrial fission proteins indicative of fragmentation [18], and activation of mitochondrial-mediated intrinsic apoptosis pathway [11].…”
Section: Mitochondrial Dysfunction In Fecdmentioning
confidence: 99%
“…In FECD, CEnCs exhibits stress-induced senescence [8], oxidant-antioxidant imbalance [9], mitochondrial DNA damage [10] and dysfunction [11], sustained unfolded protein response (UPR) [12,13], and endoplasmic reticulum (ER) stress [14]. Among these factors, mitochondrial stress [15][16][17][18] plays an important role in FECD pathogenesis. Maintaining functional mitochondria is the key to the ion pump function in CEnCs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the mechanism of ultrasonic diagnosis may be related to the changes of nuclear size and acoustic characteristics, which are related to cell death, especially the form of apoptosis [10] . Through the preliminary study of the effect of apoptosis on corneal cells caused by ultrasound irradiation time, this experiment preliminarily shows the role of apoptosis in the metabolism of normal cornea and the occurrence and development of some keratopathy, and attempts to study the changes of corneal cell apoptosis after diagnostic ultrasound irradiation in rats in order to find the safe range of diagnostic ultrasound examination.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…The exact cause of FECD is yet to be determined but evidence has shown that oxidative stress and mitochondrial dysfunction are implicated 8 , 9 . In a previous study, we have shown that oxidative stress and mitochondrial dysfunction are linked in a mitochondrial overuse vicious cycle we called mitochondrial burnout cycle 10 . In this cycle, cells are progressing through different stages that can be sorted using mitochondrial mass.…”
Section: Introductionmentioning
confidence: 99%
“…To respond to the increased energetic demand, these cells increase their mitochondrial mass, which leads to an increased production of reactive oxygen species (ROS). These ROS further damage the cells that will eventually trigger mitophagy and apoptosis 10 .…”
Section: Introductionmentioning
confidence: 99%